Experimental investigation on PCM cold storage integrated with ejector cooling system - Chen, Xiangjie; Worall, Mark; Omer, Siddig; Su, Yuehong; Riffat, Saffa (Elsevier, 2014)
An experimental investigation on the operating characteristics of cold storage ejector cooling system with finned tube inside a cylindrical PCM tank was presented in this paper. The PCM cold storage tank was coupled with the evaporator to store the excess cooling capacity of ejector cooling system and provide cooling effect when the ejector did not operate. Medium temperature source (from solar collector or industrial waste) at temperature of 120 °C was the main driving force for ejector cooling system. The performance parameters, such as temperature inside the PCM tank, inlet and outlet temperature of heat transfer fluid, cold storage rate and cold storage capacity were measured at various mass flow rates, at the evaporator temperature of 3–5 °C. The same testing parameters were measured for discharging process at the heat source temperature of 25 °C. The experimental results demonstrated that the PCM cold storage integrated with ejector could help to maintain a more stable COP for ejector cooling system. The effectiveness-NTU method was applied for characterizing the tube-in tank PCM storage system. The correlation of effectiveness as the function of mass flow rate was derived from experimental data, and was used as a design parameter for the PCM cold storage system.